2015
DOI: 10.1186/s12955-015-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Self- and proxy reports of quality of life among adolescents living in residential youth care compared to adolescents in the general population and mental health services

Abstract: BackgroundChild welfare services are aimed at providing care and protection, fostering well-being and prosocial behaviour. Thus, Quality of Life (QoL) should be an important outcome measure in Residential Youth Care (RYC) institutions. However, the dearth of research in this area gives rise to serious concern. The present study is the first large scale, nationwide study assessing QoL among adolescents living in RYC. To provide a reference frame, adolescent self- and primary contact proxy reports were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 56 publications
3
29
1
Order By: Relevance
“…This suggests that primary contacts do not notice the negative impact of maltreatment histories and number of types of adversities on different QoL subdomains, which is clear from the self-reports. In a previous study on the same population, significant differences were reported between self-and proxy reports on only the Physical Well-being and Friends subdomains, suggesting that primary contacts could serve as satisfactory substitutes for QoL information when selfreports are unavailable [26]. By contrast, the results of the present study suggest that primary contacts may not be reliable reporters of adolescents' QoL, at least not for adolescents with maltreatment histories.…”
Section: Proxy Report Reliabilitycontrasting
confidence: 93%
See 3 more Smart Citations
“…This suggests that primary contacts do not notice the negative impact of maltreatment histories and number of types of adversities on different QoL subdomains, which is clear from the self-reports. In a previous study on the same population, significant differences were reported between self-and proxy reports on only the Physical Well-being and Friends subdomains, suggesting that primary contacts could serve as satisfactory substitutes for QoL information when selfreports are unavailable [26]. By contrast, the results of the present study suggest that primary contacts may not be reliable reporters of adolescents' QoL, at least not for adolescents with maltreatment histories.…”
Section: Proxy Report Reliabilitycontrasting
confidence: 93%
“…In the Adverse Childhood Experiences (ACE) study, adversities included child abuse (physical, sexual and emotional abuse), neglect (emotional and physical) and household dysfunction (mother treated violently, household substance abuse, mental illness in the household, parental separation or divorce, or criminal household member) (25,26). However, adolescents can be exposed to many kinds of adversities and victimization.…”
Section: Childhood Adversity 131 Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Norway, foster care is the preferred form of placement and RYC institutions are a last resort [1,2]. Adolescents in RYC therefore represent a high-risk population for serious psychopathology, having a very high prevalence of mental disorders and a poorer quality of life (QoL) in most life domains compared to their peers in the general population [3,4]. Hence, child welfare services should foster wellbeing and QoL and ensure that residents in institutions gain access to evidence-based psychiatric treatment for their psychopathology.…”
Section: Introductionmentioning
confidence: 99%